Effects of foliar conditioners on safety production of main rice varieties in cadmium-contaminated farmland in eastern Zhejiang Province - ZHOU Qiyao; NI Yuanjun; XU Shun’an; WANG Qiong; ZHAN Lichuan; FENG Ying (浙江大学学报. 农业与生命科学版)
Application of foliar conditioner is an important technical measure to reduce the contents of heavy metals in edible parts of crops and realize the safe utilization of moderately and slightly polluted farmlands. In this study, the effects of different ion antagonistic foliar conditioners and the optimal conditioner on the safety of rice production were compared through two consecutive years of field experiments. The field plot experiment results showed that five kinds of foliar conditioners had obvious effects on reducing cadmium (Cd) content and increasing yield in the two sites, among which spraying multiple compound foliar conditioner had the best effect on reducing Cd content in rice, and Cd contents in the brown rice in two sites decreased by 13.0% and 14.5%, respectively. Furthermore, the effects of foliar application of the multiple compound conditioner on rice yields and Cd contents of seven main rice varieties in eastern Zhejiang Province were compared through regional experiments. The results showed that the foliar application of multiple compound conditioner could increase rice yield by 8.2%-10.8% and decrease Cd content of the brown rice by 15.7%-20.3%. Among them, YY17 combined with the foliar application of multiple compound conditioner had the lowest Cd content in the brown rice. These results indicate that the combination of low accumulation varieties and the selected multiple compound conditioner could effectively reduce the Cd content in brown rice, achieve the safe utilization of farmland with slight Cd pollution, and promote the yield and efficiency of rice production.